Efeitos de diferentes inclusões da snaplage na dieta sobre a digestão e fermentação ruminal de novilhos de corte - Justino, Túlio Gomes (2021)
The objective of this study was to evaluate the ruminal and metabolic parameters of Nelore steers fed diets containing different proportions of snaplage. Six nelore steers were used, castrated, with an average weight of 422 kg, with an average age of 24 months with cannula in the rumen. The experimental diets were: SNAP0 (whole plant corn silage, reconstituted corn grain silage, dry ground corn grain, soybean meal, cottonseed meal, urea and mineral and vitamin); SNAP65 (snaplage 65%, dry ground corn, soybean meal, cottonseed meal, urea and mineral and vitamin) and SNAP85 (snaplage 85%, soybean meal, cottonseed meal, urea and mineral and vitamin). Three diets and three experimental periods were used, used 2 simultaneous Latin Squares with duration of 66 days, which were repeated for another 66 days, with the purpose of, at the end of the general experimental period, 4 Latin Squares 3x3. With the increase in the proportion of snaplage, there was an increase in the consumption of dry matter and, consequently, of other nutrients as well (P<0.01). Using snaplage reduces the digestibility of starch and other nutrients in the rumen but increases post-rumen digestibility. Consequently, a higher pass rate results. The total digestibility of crude protein and NDF are higher when using snaplage, as the fiber contained in the straw has a lower proportion of lignin when compared to the fiber from the stalk. Due to the physically effective NDF of the diets, there was no incidence of clinical and subclinical acidosis during the experiment. There was no statistical difference in microbial protein production (P=0.36). SNAP65 and SNAP85 are diets that result in good ruminal and metabolic parameters. But the SNAP85 treatment has better digestible results in the whole tract.